RANCANG BANGUN MESIN POLES UNTUK PROSES METALOGRAFI - Herdiana, Ade; Abidin, Zenal (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
A polishing and sanding machine is a tool that works using electrical energy, to determine the particle elements of a material there are several tests that must be carried out, one of which is metallography testing. The metallographies process aims to see the microstructure of a material. Metals is a science that studies metal materials, this science develops not only on the basis of theory but on the basis of observation, testing and measurement. The process begins with the installation, grinding, polishing, etching, and continues with observation under a microscope. The working principle of the tool is to polish the test object using coarse, medium, fine and very fine sandpaper. The mechanical properties of a metal or alloy can be observed, one of which is by analyzing the microstructure of the material. The metallographies test carried out aims to observe the microstructure. In the process of working on metallographies testing samples involving polishing and sanding machines. The formulation of the problem in designing this polishing and sanding machine is "How to design the construction of the polishing and sanding machine provided that the frame can withstand the loads from the forces that occur when the polishing and sanding machine operates, How to design the construction of an appropriate polishing and sanding machine, efficient & ergonomics”. The design of this polishing machine begins with designing a polishing machine using the FEM method, then selecting components, making components. Component assembly, and polishing machine testing.